Analisis Bangkitan Perjalanan Berbasis Rumah Tangga (Studi Kasus: Perumahan Karangploso View, Kabupaten Malang) - Cruz , Maria Fujiada Da; Arifianto , Andy Kristafi; Sa'dillah, M. (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
The increasing population of Malang Regency can trigger increased movement. The large number of housing estates that have emerged in Malang Regency will lead to an increase in the number of movements made by residents who occupy housing in an effort to meet their needs, be it primary, secondary, and tertiary needs which can cause traffic flow disruptions that cause a decrease in the level of road service. The main objective of the study is trip generation to obtain a relationship that connects land use with the amount of development entering and leaving the area. The trip generation planning plan to assess as accurately as possible the current traffic age, which will be used to predict what will happen. This survey was conducted by interviewing and distributing questionnaires to each resident's house. Analyzing data with descriptive statistical methods of correlation test and multiple linear regression analysis. Based on the results of the analysis that has been obtained, the characteristics of the population in Karangploso View housing are the number of family members who dominate 4 people consisting of family members who go to school and work with an average income of >Rp 2,000,000.00. The most dominating vehicle is a 2-wheeled vehicle and is most often used to go to the office / office. The results of the analysis show that the frequency of use of 2-wheeled vehicles in a week has a significant influence on trip generation with a regression coefficient value of 0.524. Thus, along with the increase in population, the number of trips using 2-wheeled and 4-wheeled vehicles increased significantly, especially on routine trips such as going to work also increased significantly.